Molecular detection and phylogeny of Anaplasma spp. in cattle reveals the presence of novel strains closely related to A. phagocytophilum in Turkey - Aktas, Munir; Colak, Serdar (Elsevier Gmbh, 2021)
Anaplasma species are obligate intracellular rickettsial pathogens that affect the health of humans and animals. In this study, we investigated the presence and frequency of Anaplasma species by 16S rRNA PCR-RLB, RFLP, and DNA sequencing in 200 apparently healthy cattle. Anaplasma spp. overall infection rate was 38.5 % (77/200) by RLB. The frequency of single and mixed infections was 31.5 % (63/200) and 7% (14/200), respectively. The most common species was A. marginale (32.5 %), followed by A. centrale (5.5 %), Anaplasma/Ehrlichia catc-all (5.5 %) and Anaplasma sp. Omatjenne (2.5 %). No A. phagocytophilum and A. bovis were detected in the tested animals. Eleven of 77 PCR-positive amplicons gave positive reactions to the catch-all probes but did not show any signals to the species-specific probes, but PCR-RFLP results showed that these amplicons were A. phagocytophilum-like 1 and A. phagocytophilum-like 2 strains. Sequencing and phylogenetic analyses based on 16S rRNA gene validated RFLP findings and provided evidence for the circulation of A. phagocytophilum-like-1 and 2 strains in Turkish cattle. This is the first report of the presence of A. phagocytophilum-like strains in the country. These findings indicate that A. phagocytophilum-like 1 and 2 strains should be taken into account in the differential diagnosis with bovine anaplasmosis.
Keywords: Anaplasma phagocytophilum; Reverse line blot; Cattle